The ruling on selling and purifying feline curtains in the narrations of Imam al-Sadiq, “peace be upon him” (Journal of the College of Basic Education, 2025)
My research entitled " The Ruling on Selling and Purifying the Leftovers of Cats in the Narrations of Imam al-Sadiq (peace be upon him)" deals with the ruling on selling and purifying the leftovers of cats in light of the narrations reported from Imam al-Sadiq, due to the importance of purity in our true religion, as it is a condition for the validity of many acts of worship in Islam. The Ahl al-Bayt School has undertaken to interpret and clarify what came in the Prophetic Sunnah, and there is no doubt that the Prophetic Sunnah was concerned with clarifying the foundations of life that guarantee human rights and his relationship with other creatures, and regulated the relationship between them, and clarified the purity and impurity of creatures and the ruling on selling them and how to deal with them, as the Noble Messenger (may God bless him and his family) and his pure family called for kindness to animals and feeding them, protecting them from aggression, and being kind to them.